Fire needle therapy for the treatment of cancer pain: a protocol for the systematic review and meta-analysis - Zhang, Junning; Ren, Yuehan; Wu, Weizhen; Yuan, Yi; Wang, Jiale; Tang, Yi; Zhou, Yunqiao; Qiao, Yizhuo; Liu, Baoqin (Frontiers in Neurology, 2024)
Background Cancer patients frequently suffer pain as one of their symptoms. It includes acute and chronic pain and is one of the most feared symptoms for patients. About one-third of adults actively undergoing cancer treatment suffer from pain related to their condition. Cancer pain control remains suboptimal due to a lack of assessment, knowledge, and access. Fire needle therapy, a traditional Chinese medicine, offers a potentially beneficial addition to current pain management approaches. This protocol outlines a systematic review and meta-analysis to compile evidence and examine the pain-relieving effects and safety of fire needle therapy for cancer patients. Methods and analysis We will systematically search China National Knowledge Infrastructure (CNKI), Wanfang Database, China Biology Medicine disc (CBM), China Science and Technology Journal Database (CSTJ or VIP), PubMed, Web of Science, Embase, Cochrane Central Registry of Controlled Trials (CENTRAL), Chinese Clinical Trial Registry (Chictr), Opengrey, Worldcat, and Scopus from inception through July 2023. Random control trials (RCTs) include all types of cancer patients (age ≥ 18 years) complaining of pain. The primary outcome will be changes in pain intensity measured by Visual Analogue Scale (VAS), Numerical Rating Scale (NRS), Neuropathic Pain Scale (NPS), or Brief Pain Inventory (BPI). Secondary outcomes include quality of life (EORTC QLQ-C30 and GCQ), performance status (KPS), times of burst pain, treatment response rate, the dose reduction of analgesic drugs, and side effects rates. Utilizing the Cochrane risk bias measurement tool: Risk of Bias 2 (RoB 2), the trials’ quality will be evaluated, and meta-analysis will be performed using RevMan software (version 5.4). Discussion This systematic review will be the first comprehensive review of the literature to provide a meta-analysis of fire needle therapy for cancer pain, including only Random control trials (RCTs). For the sake of transparency and to avoid future duplication, the publication of this protocol offers a clear illustration of the procedures utilized in this evaluation. The results of our future studies may provide a new approach and theoretical basis for the treatment of cancer pain by medical oncology professionals. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023418609.